2013
DOI: 10.5194/nhess-13-1567-2013
|View full text |Cite
|
Sign up to set email alerts
|

Coupled atmosphere ocean climate model simulations in the Mediterranean region: effect of a high-resolution marine model on cyclones and precipitation

Abstract: In this study we investigate the importance of an eddy-permitting Mediterranean Sea circulation model on the simulation of atmospheric cyclones and precipitation in a climate model. This is done by analyzing results of two fully coupled GCM (general circulation models) simulations, differing only for the presence/absence of an interactive marine module, at very high-resolution (~ 1/16°), for the simulation of the 3-D circulation of the Mediterranean Sea. Cyclones are tracked by applying an objective Lagrangian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 55 publications
(57 reference statements)
2
26
0
1
Order By: Relevance
“…These studies have shown that two-way, high-frequency interactions and higher SST spatial resolution improve the representation of surface heat fluxes, hydrological parameters, winds, and extremes events (e.g., cyclogenesis, medicanes, and heavy precipitation events) in the Mediterranean region (Lebeaupin Brossier and Drobinski 2009;Sanna et al 2013;Lebeaupin Brossier et al 2014;Akhtar et al 2014). In a recent study, Panthou et al (2016) show that high-resolution regional atmospheric models coupled with Mediterranean Sea models improve the representation of hot days and droughts more than heavy precipitation events.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have shown that two-way, high-frequency interactions and higher SST spatial resolution improve the representation of surface heat fluxes, hydrological parameters, winds, and extremes events (e.g., cyclogenesis, medicanes, and heavy precipitation events) in the Mediterranean region (Lebeaupin Brossier and Drobinski 2009;Sanna et al 2013;Lebeaupin Brossier et al 2014;Akhtar et al 2014). In a recent study, Panthou et al (2016) show that high-resolution regional atmospheric models coupled with Mediterranean Sea models improve the representation of hot days and droughts more than heavy precipitation events.…”
Section: Introductionmentioning
confidence: 99%
“…We have to keep in mind that most of the published RCSMs were forced by the ERA-40 reanalysis (Artale et al, 2010;Herrmann et al, 2011;Carillo et al, 2012;L'He´ve´der et al, 2013) or by GCMs Krzic et al, 2011;Carillo et al, 2012;Dell'Aquila et al, 2012;Dubois et al, 2012;Rojas et al, 2013;Sanna et al, 2013) Dubois et al (2012), Gualdi et al (2013a)]. Note that reanalysis-driven simulations are expected to perform better than GCM-driven simulations, as their lateral boundary conditions can be considered more realistic.…”
Section: Comparison Of Cnrm-rcsm4 With the Stateof-the-art Mediterranmentioning
confidence: 99%
“…SW bias in CNRM-RCSM4 (Sanchez-Gomez et al, 2011;Dubois et al, 2012), which explains the very good behaviour of the model in SSS and salt content. The model SST cold bias is present in most of the other ERA40-driven RCSMs (Li et al, 2012) and GCM-driven RCSMs Sanna et al, 2013) except for the LMDZ-Med/ NEMOMED8 model, which shows nearly no SST bias (L'He´ve´der et al, 2013). However, despite spatial biases, the SSS simulated by CNRM-RCSM4 has the smallest bias on average over the Mediterranean Sea among the published RCSMs, with most of the other RCSMs showing an overestimated SSS L'He´ve´der et al, 2013;Di Luca et al, 2014).…”
Section: Comparison Of Cnrm-rcsm4 With the Stateof-the-art Mediterranmentioning
confidence: 99%
“…Recent studies show that high-resolution coupled models over the Euro-Mediterranean region significantly improve the representation of air-sea fluxes Dubois et al, 2012;Artale et al, 2010;Somot et al, 2008). In another study, Sanna et al (2013) have shown that SSTs simulated through a high-resolution eddypermitting ocean model have strong and beneficial effects on precipitation and cyclogenesis simulation.…”
Section: Introductionmentioning
confidence: 99%